Palaeodiet and animal husbandry in a changing environment from the Mesolithic to the Viking Age in the Limfjord area, Denmark, from δ13C and δ15N analyses. (December 2021) - van der Sluis, L.G.; Reimer, P.J.
Highlights: Stable isotope results from the Limfjord area show dietary changes through time. Iron Age δ 15 N values elevation due to fertiliser usage and aquatic protein intake. Higher δ 15 N values in sheep/goats than cattle indicate different feeding strategies. People adjusted their lifestyle in response to environmental changes. Abstract: Despite the rich archaeological heritage present in the Limfjord region in Denmark, few palaeodietary studies using human and animal bone material from this area currently exist. This paper aims to investigate the palaeodiet as well as animal husbandry strategies in this region during prehistoric times, from the Mesolithic to the Viking Age using stable isotope analysis. New stable isotope results from almost 300 human and animal bones are presented here, as well as their comparison with previously published data. Higher δ 15 N values in sheep/goats than cattle suggest that cattle were more confined while the sheep/goats were allowed to roam and possibly consume salt-marsh grass. The stable isotope results reveal a rise in δ 15 N ratios in human individuals from the Iron Age, which is most likely related to the combined effects of fertilisation practices and aquatic protein consumption. Additionally, evidence for marine exploitation in the form of shell middens and fish remains can be linked to periods characterised by climatic deterioration.